Role of Primary Care Clinicians in the Diagnosis and Treatment of LUTS and BPH - Kuritzky, Louis (MedReviews, LLC, 2004)
Primary care clinicians are often responsible for the treatment of lower urinary tract symptoms (LUTS) and benign prostatic hyperplasia (BPH). The combination of the compelling epidemiologic presence of BPH, compromised quality of life due to LUTS, and the availability of highly effective oral therapeutic agents, offers an opportunity for substantial clinical impact in the primary care setting. Evolving management pathways include utilization of both symptom-modifying treatment and disease-modifying treatment. Alpha blockers are excellent to provide symptomatic treatment, but do not alter long-term disease progression. Alpha reductase inhibitors provide therapy by reducing the need for surgical intervention and the incidence of acute urinary retention. The combination of alpha blockers and alpha reductase inhibitors will be best for some patients, typically those with large prostate glands in whom disease progression is most likely. Primary care clinicians will want to become more familiar with recent clinical trails that are shaping emerging therapeutic practice.